2020
DOI: 10.25259/sni_568_2019
|View full text |Cite
|
Sign up to set email alerts
|

Current advancements in the management of spinal cord injury: A comprehensive review of literature

Abstract: Background: Spinal cord injury (SCI) carries debilitating lifelong consequences and, therefore, requires careful review of different treatment strategies. Methods: An extensive review of the English literature (PubMed 1990 and 2019) was performed regarding recent advances in the treatment of SCI; this included 46 articles written over 28 years. Results: Results of this search were divided into five major modalities; neuroprotective and neuroregenerative pharmaceuticals, neuromodulation, stem cell-based the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 49 publications
0
26
0
1
Order By: Relevance
“…Spinal cord injury (SCI) is a grievous neurological disease caused by traumatic and nontraumatic injuries, which leads to different degrees of sensorimotor injury and sphincter dysfunction. The incidence of SCI reaches 0.015‰ to 0.04% and the cases exceed 1 million in North America 1 3 . In addition, in Japan, the proportion of SCI in trauma patients is increasing annually 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord injury (SCI) is a grievous neurological disease caused by traumatic and nontraumatic injuries, which leads to different degrees of sensorimotor injury and sphincter dysfunction. The incidence of SCI reaches 0.015‰ to 0.04% and the cases exceed 1 million in North America 1 3 . In addition, in Japan, the proportion of SCI in trauma patients is increasing annually 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in Japan, the proportion of SCI in trauma patients is increasing annually 4 . Meanwhile, the healthcare cost is extremely high and can reach as much as $7 billion a year 1 . Studies have also shown that the incidence of SCI increases with age, peaking at 46 and 60 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Minocycline is a second‐generation semisynthetic tetracycline antibiotic with a broad spectrum and bacteriostatic features [137], which is also frequently used in clinical trials for the treatment of acne. Moreover, it may have significant neuroprotective and anti‐inflammatory effects in different models of brain injury and SCI [24,138–141]. Previous experimental and clinical studies ( Tables 2 and 3 ) have demonstrated that minocycline can improve injured cord histopathological status, functional recovery, and sensory complications after SCI [33,138,142–148].…”
Section: Antibiotics With Therapeutic Effects In Scimentioning
confidence: 99%
“…Relevant causes of neuronal lesions also include direct injuries to the nervous system due to physical traumas. Traumatic damages to the central nervous system (CNS), both at the brain and spinal cord, often cause irreversible effects and current treatment strategies do not offer safe results [5][6][7]. Unlike neurons of the CNS, the nerve fibers of the peripheral nervous system (PNS) have the ability to grow back after traumatic injury [8,9] with high reparative and regenerative activity [10,11].…”
Section: Introductionmentioning
confidence: 99%